Разработка методики выбора параметров режима бурения - Кожевников, А.А.; Мартыненко, И.И. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
In article the technique of a choice of parameters of a mode of drilling on a maximum of trip speed is resulted. The choice of parameters is carried out at carrying out of skilled drilling with cyclic change of parameter inside flight.